The threat of Alternaria Late Blight of Pistachio and its integrated management - Abdelhak Rhouma; Rabeb Rhouma; Lobna Hajji-Hedfi (Journal of Oasis Agriculture and Sustainable Development)
With the ever-increasing importance of pistachio as a crop nut worldwide, there has developed a parallel ingrowth in fungal diseases pertaining to it. Pistachio trees, being one of the few trees that grow in the Mediterranean climate, have come under several serious pathogens that endanger its very production. Such conditions, therefore, require a review of the major fungal diseases affecting pistachios: namely, Alternaria Late Blight. The biological features and morphology concerning both will be discussed for proper identification and diagnosis. Moreover, the review covers various management practices to control these diseases, which include biological control with the use of beneficial microbes, limited application of chemical fungicides, efficient methods of irrigation to minimize pathogen-conducive conditions, limitation of pathogen reservoirs by management of weeds, and growing resistant varieties of pistachio. Such integrated methods of management will contribute to better plant health and enable pistachio producers to realize full growth potential and continue yields at high levels.